2014
DOI: 10.1001/jamaophthalmol.2013.7647
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Technological Advances on Outcomes for Elderly Persons With Exudative Age-related Macular Degeneration

Abstract: IMPORTANCE Exudative age-related macular degeneration (ARMD) is the major cause of blindness among US elderly. Developing effective therapies for this disease has been difficult.OBJECTIVES To assess the effects of introducing new therapies for treating exudative ARMD on vision of the affected population and other outcomes among Medicare beneficiaries newly diagnosed as having ARMD.DESIGN The study used data from a 5% sample of Medicare claims and enrollment data with a combination of a regression discontinuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 35 publications
1
46
0
1
Order By: Relevance
“…Our observational period largely preceded the introduction of anti-VEGF therapies which occurred in 2006. 27 It is possible that given the introduction of an effective therapy, rates of eye exams would have been higher for beneficiaries diagnosed with wet AMD if our observational period had included more years following 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Our observational period largely preceded the introduction of anti-VEGF therapies which occurred in 2006. 27 It is possible that given the introduction of an effective therapy, rates of eye exams would have been higher for beneficiaries diagnosed with wet AMD if our observational period had included more years following 2006.…”
Section: Discussionmentioning
confidence: 99%
“…3 review on this topic (9) found four studies where the prevalence of depression was examined in patients receiving anti-VEGF treatments (22)(23)(24)36). Findings were preliminary but suggested that the wAMD patient group receiving anti-VEGF treatment still present higher rates of depression and anxiety in comparison with general population.…”
Section: Introductionmentioning
confidence: 99%
“…Although antiangiogenic treatments have greatly improved the prognosis of neovascular AMD, the majority of treated patients do not regain lost vision. 3,4 No medical treatment is available for patients with geographic atrophy. Thus, many patients with AMD experience irreversible vision loss, impaired functional vision, and diminished quality of life.…”
mentioning
confidence: 99%